Puberty and Epilepsy Onset in Women - Galina Odintsova; Nina Dengina (Archives of Epilepsy, 2024)

(untitled)
Objective: The significance of the onset of seizure based on the medical and social aspects of epilepsy. The aim of this study was to investigate the age of seizure onset based on the specific characteristics of each age of seizure onset in many epilepsy syndromes to make an appropriate diagnosis. Methods: The age at epilepsy was retrospectively studied in 155 women aged between 16 and 45 years with a verified diagnosis of epilepsy. The epidemiological method revealed the age at epilepsy onset, and females were divided into three groups: pre-puberty (10-11 years old), puberty (10-18 years old), and post-puberty (18+ years old). A correlation study of the frequency of onset with the periods of formation and function of the female reproductive tract was conducted. Results: A statistically significant quantitative predominance of females with epilepsy onset during puberty (p<0.001) was identified. Statistically valid was the prevalence of epilepsy onset in the combined age range of 12 to16 (p<0.001). A direct link between menarche and epilepsy onset was detected in the general cohort in 13% of females, which is among the risk factors for catamenial seizure onset. Conclusion: Epilepsy onset in females of reproductive age dominates during childhood development. In more than half of the cases, the epilepsy onset occurs in the puberty period. Epilepsy onset most often occurs between the ages of 12 and 16. Seizure onset occurs at the ages of 12-16 years during menstrual bleeding and ovulatory cycle development due to the proconvulsive effects of estrogens.